2013
DOI: 10.1371/journal.pone.0064478
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Biotic and Abiotic Stresses on the Competitive Ability of Multiple Herbicide Resistant Wild Oat (Avena fatua)

Abstract: Ecological theory predicts that fitness costs of herbicide resistance should lead to the reduced relative abundance of resistant populations upon the cessation of herbicide use. This greenhouse research investigated the potential fitness costs of two multiple herbicide resistant (MHR) wild oat (Avena fatua) populations, an economically important weed that affects cereal and pulse crop production in the Northern Great Plains of North America. We compared the competitive ability of two MHR and two herbicide susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Under non‐competitive conditions in the greenhouse, photosynthetic and relative growth rates were not different between susceptible and MHR plants, but MHR plants produced fewer tillers and seeds than susceptible plants . However, a second greenhouse study showed that there were no differences in competitive abilities between susceptible and MHR plants under gradients of biotic (competition with Triticum aestivum ) and abiotic (limiting nitrogen) stresses . Fitness comparisons have not been conducted under field conditions.…”
Section: Multiple Herbicide Resistant Avena Fatuamentioning
confidence: 99%
See 1 more Smart Citation
“…Under non‐competitive conditions in the greenhouse, photosynthetic and relative growth rates were not different between susceptible and MHR plants, but MHR plants produced fewer tillers and seeds than susceptible plants . However, a second greenhouse study showed that there were no differences in competitive abilities between susceptible and MHR plants under gradients of biotic (competition with Triticum aestivum ) and abiotic (limiting nitrogen) stresses . Fitness comparisons have not been conducted under field conditions.…”
Section: Multiple Herbicide Resistant Avena Fatuamentioning
confidence: 99%
“…89 However, a second greenhouse study showed that there were no differences in competitive abilities between susceptible and MHR plants under gradients of biotic (competition with Triticum aestivum) and abiotic (limiting nitrogen) stresses. 97 Fitness comparisons have not been conducted under field conditions.…”
Section: Multiple Herbicide Resistant Avena Fatuamentioning
confidence: 99%
“…In the continuous wheat and wheat ‐ fallow cropping systems, MHR mean seedbank densities of both populations were negatively impacted by increasing N fertilisation rate. While previous glasshouse (Blackshaw & Brandt, ; Lehnhoff et al ., ) and field (Carlson & Hill, ; Ross & Van Acker, ) research determined that N fertilisation has a neutral or positive effect on A. fatua growth and competitive ability with wheat , our study demonstrated the opposite.…”
Section: Discussionmentioning
confidence: 41%
“…From each generation of 50 plants, all seeds were harvested and a random selection of 50 seeds was used to initiate five additional generations without herbicide selection to homogenise the genetic background. These two populations were used to successfully characterise the biochemical mechanisms responsible for MHR (Burns et al ., ; Keith et al ., ), as well as the physiological and ecological consequences of MHR (Lehnhoff et al ., ,b). The susceptible HS1 population was derived from seeds of untreated plants bordering an adjacent barley production field, grown for seven generations as described for MHR3–4 except without herbicide selection, and was confirmed to be 100% susceptible to field rates of the herbicide used in this study (Lehnhoff et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…A. fatua populations that are resistant to one or more herbicides have been reported in the USA [6][7][8] and elsewhere [1]. We recently described the A. fatua MHR3 and MHR4 populations that are resistant to the acetyl-CoA carboxylase (ACCase) inhibitors fenoxaprop-P-ethyl, tralkoxydim, and pinoxaden, the acetolactate synthase (ALS) inhibitors imazamethabenz-methyl and flucarbazone, the growth inhibitor difenzoquat, the photosystem I inhibitor paraquat (MHR3 only), and the very long chain fatty acid (VLCFA) biosynthesis inhibitor triallate, with resistant/susceptible ED 50 ratios ranging from 1.4 to 57 [6,9]. The MHR A. fatua populations are thus resistant to members of all selective herbicide families available for A. fatua control in U.S. small grain production.…”
Section: Introductionmentioning
confidence: 99%